SHAXSDA RUHIY VA JISMONIY SALOMATLIK - Zaripov, O.M. (SCIENCE and SOCIETY, 2024)
The scientific article expresses the importance and relevance of health protection, human well-being, life expectancy, active and decent work, development, physical and mental health. The article provides specific completion recommendations.